Risk Factors for Intestinal Parasitosis among Almajiri Pupils in Zaria, North Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Intestinal parasitosis is an infection by intestinal parasites and is of important public health concern in the tropics and subtropics. The Almajiri pupils have peculiar characteristics in the community that predispose them to intestinal parasitosis.Aim:To assess the risk factors for intestinal parasitosis among Almajiri pupils in Zaria, North Western Nigeria.Settings and Design:The study was undertaken in Zaria town of Kaduna State, North Western Nigeria. Cross-sectional analytical design was used for this study.Subjects and Methods:A structured questionnaire was used to obtain data on 262 consented participants drawn by multistage sampling technique. Sociodemography, risk factors for intestinal parasitosis, and stool examination findings of the study participants were assessed.Statistical Analysis Used:Descriptive and inferential statistics were used to analyze the data.Pvalues